Roehana Koeddoes’s Resistance to Dutch Colonialism in “Belenggu Emas” by Iksaka Banu - Rahmi Rahmayati (Humaniora, 2021)
Despite being positioned as inferior by the colonial and patriarchal systems of the time, Indonesian women were involved in the resistance against Dutch colonization. Now recognized as national heroes, these women took part in the struggle by directly participating in fighting, or indirectly through social initiatives. Among them was Roehana Koeddoes, whose resistance is depicted in the short story, “Belenggu Emas”, by Iksaka Banu, wherein an indigenous woman from West Sumatra establishes a school dedicated to teaching women and a newspaper, Soenting Melajoe, published by and for women. This study aimed to represent Roehana Koeddoes’s resistance to Dutch colonialism in Banu’s story, using a qualitative method with a post-colonial theory approach. The results showed that Roehana Koeddoes’s resistance to Dutch colonialism was in the form of mimicry, hybridity, and ambivalence. The mimicry shown is the imitation of the colonial discourse regarding superiority of knowledge, education, ethics, and habits, as demonstrated by Roehana Koeddoes’ intellectual abilities in expressing her courage and opinion, through both her writings in the newspapers she owned and her activism as an educationalist and journalist, which inspired women across the Dutch East Indies, including Dutch women. Resistance in the form of hybridity occurs through spatial planning, which is indicated by the adoption of houses with Europeanstyle windows and the arrangement of living room corners that combine Eastern and Western cultures. Lastly, resistance in the form of ambivalence is shown by the attitude of the character, Roehana Koeddoes, who at equal times shows her eastern and western sides.